Positive electrode containing positive electrode additive, method for manufacturing positive electrode, and lithium secondary battery containing positive electrode
By adjusting the coating temperature of the slurry during the manufacturing process of the positive electrode of the lithium secondary battery, the problem of battery characteristics deterioration caused by temperature deformation of the positive electrode additive is solved, and higher battery performance and life are achieved.
Patent Information
- Application Number
- CN202280005390.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-02
- Filing Date
- 2022-05-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-06
AI Technical Summary
When manufacturing the positive electrode, the positive electrode additive deteriorates the battery characteristics due to structural deformation caused by temperature.
By adjusting the coating temperature of the slurry during the production of the positive electrode, the formation temperature of the first and second mixture layers is controlled to be below 40°C, and deformation of the positive electrode additive is reduced.
It effectively prevents structural deformation of the positive electrode additive and improves the performance and life of the lithium secondary battery.
Smart Images

Figure BDA0004029306440000131 
Figure BDA0004029306440000151
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode including a positive electrode additive, a method for manufacturing the positive electrode, and a lithium secondary battery including the positive electrode, wherein deformation due to temperature is minimized by adjusting the coating temperature of a slurry when manufacturing the positive electrode.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0071225 filed on June 2, 2021, and incorporates the entire contents of the Korean Patent Application by reference. Background Art
[0003] Recently, the demand for secondary batteries as energy sources is rapidly increasing. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used.
[0004] Graphite is mainly used as the negative electrode material of lithium secondary battery, but because graphite has a small unit mass capacity of 372mAh / g, it is difficult to increase the capacity of lithium secondary battery. Therefore, in order to increase the capacity of lithium secondary battery, negative electrode materials that form intermetallic compounds with lithium, such as silicon, tin and oxides thereof, are being developed and used as non-carbon-based negative electrode materials with higher energy density than graphite. However, in the case of such non-carbon-based negative electrode materials, the problem is that, although the capacity is large, the initial efficiency is low, the lithium consumption during the initial charge and discharge is large, and the irreversible capacity loss is large.
[0005] In this regard, a method of providing a lithium ion source or storage for a positive electrode material and overcoming the irreversible negative electrode capacity loss has been proposed, which uses a material that is electrochemically active after the first cycle so as not to deteriorate the overall performance of the battery. Specifically, a method of applying an oxide containing excess lithium (e.g., Li6CoO4) as a sacrificial positive electrode material or an irreversible additive (or overdischarge inhibitor) to the positive electrode is known.
[0006] Meanwhile, conventional cathode additives such as Li6CoO4 show excellent charge / discharge characteristics and life characteristics, but have the problem of low thermal stability. Specifically, when manufacturing the mixture layer of the cathode, the cathode additives may cause problems such as structural deformation caused by the influence of temperature (e.g., slurry temperature) and deterioration of battery characteristics.
[0007] Therefore, there is a need for the development of a technology capable of preventing the structure of the positive electrode additive from being deformed even when the positive electrode additive is used in the production of the positive electrode.
[0008] [Related technical literature]
[0009] [Patent Document]
[0010] Japanese Patent Publication No. 2019-061751 Summary of the invention
[0011] [Technical issues]
[0012] An object of the present invention is to provide a positive electrode including a positive electrode additive, a method of manufacturing a positive electrode, and a lithium secondary battery including the positive electrode, wherein deformation due to temperature is minimized by adjusting a coating temperature of a slurry when manufacturing the positive electrode.
[0013] [Technical solution]
[0014] The present invention aims to solve the above problems and provides a method for manufacturing a positive electrode for a lithium secondary battery, the method comprising: coating a first slurry containing a positive electrode active material, a positive electrode additive, a conductive material and a binder on one surface or both surfaces of a current collector and forming a first mixture layer, and coating a second slurry containing a positive electrode active material, a conductive material and a binder on the current collector formed with the first mixture layer and forming a second mixture layer, wherein the formation of the first mixture layer and the formation of the second mixture layer respectively include a process of controlling the temperature of the first slurry to be below 40° C. and a process of controlling the temperature of the second slurry to be below 40° C., and when the first mixture layer is subjected to X-ray diffraction (XRD) analysis, the following expression 1 is satisfied:
[0015] [Expression 1]
[0016] A / B≤1
[0017] A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°.
[0018] The forming of the first mixture layer and the forming of the second mixture layer may include a process of controlling the temperature of the first slurry to be 10° C. to 40° C. and a process of controlling the temperature of the second slurry to be 10° C. to 40° C., respectively.
[0019] The method may further include a first rolling operation of rolling the first mixture layer after forming the first mixture layer, and a second rolling operation of rolling the second mixture layer after forming the second mixture layer.
[0020] The first rolling operation may be performed at a speed of 0.5 m / s to 6 m / s, the second rolling operation may be performed at a speed of 2 m / s to 7 m / s, and the second rolling operation may be performed at a speed greater than the first rolling operation. In this case, the first rolling operation may be performed at a temperature of 10° C. to 40° C., and the second rolling operation may be performed at a temperature of 40° C. to 100° C.
[0021] The present invention also aims to provide a positive electrode for a lithium secondary battery, the positive electrode comprising a current collector and a mixture layer formed on one surface or both surfaces of the current collector, wherein the mixture layer has a double-layer structure in which a first mixture layer and a second mixture layer are laminated, the first mixture layer contains a positive electrode active material, a conductive material, a positive electrode additive and a binder, and when the first mixture layer is subjected to XRD analysis, the following expression 1 is satisfied:
[0022] [Expression 1]
[0023] A / B≤1
[0024] A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°.
[0025] The positive electrode additive may be lithium cobalt oxide represented by the following chemical formula 1:
[0026] [Chemical formula 1]
[0027] Li p Co (1-q) M 1 q O4
[0028] In the above chemical formula 1, M 1 It can represent one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
[0029] In the above chemical formula 1, M 1 represents a Zn element, and q may be 0.2≤q≤0.4.
[0030] The positive electrode additive may have a tetragonal structure with a space group of P42 / nmc.
[0031] The content of the positive electrode additive may be 0.1 wt % to 5 wt % with respect to the total weight of the first mixture layer.
[0032] The positive electrode active material may be a lithium nickel composite oxide represented by the following Chemical Formula 2:
[0033] [Chemical formula 2]
[0034] Li x [Ni y Co z Mn w M 2v ]O u
[0035] In the above chemical formula 2, M 2 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 <z≤0.5,0.01<w≤0.5,0≤v≤0.2,1.5≤u≤4.5。
[0036] The average thickness ( D1 ) of the first mixture layer may be 0.1 μm to 20 μm, and the average thickness ( D2 ) of the second mixture layer may be 50 μm to 300 μm.
[0037] The present invention also aims to provide a lithium secondary battery, which comprises the positive electrode and negative electrode of the present invention as described above, and a separator between the positive electrode and the negative electrode.
[0038] The negative electrode may include a negative electrode current collector and a negative electrode mixture layer located on the negative electrode current collector and including a negative electrode active material, wherein the negative electrode active material may include a carbon material and a silicon material.
[0039] The silicon material may be included in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the negative electrode mixture layer.
[0040] [Beneficial Effects]
[0041] By adjusting the coating temperature of the slurry when manufacturing the positive electrode, the positive electrode containing the positive electrode additive, the method for manufacturing the positive electrode, and the lithium secondary battery including the positive electrode of the present invention can minimize the deformation of the positive electrode additive due to temperature, and thus can prevent the structural deformation of the positive electrode additive contained in the positive electrode. DETAILED DESCRIPTION
[0042] The present invention is susceptible to various modifications and alternative forms, and specific embodiments thereof will be described in detail.
[0043] It should be understood, however, that the invention is not to be limited to the particular forms disclosed, but on the contrary, the invention is to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the invention.
[0044] It should also be understood that when used herein, the terms "comprise / include" indicate the presence of stated features, integers, steps, operations, components, parts or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, operations, components, parts or combinations thereof.
[0045] In addition, when a layer, film, region or plate is referred to as being "formed on" another layer, film, region or plate, it includes the case where the layer, film, region or plate is directly formed on the other layer, film, region or plate, and the case where another layer, film, region or plate is inserted between the layer, film, region or plate and the other layer, film, region or plate. In contrast, when a layer, film, region or plate is referred to as being "formed under" another layer, film, region or plate, it includes the case where the layer, film, region or plate is directly formed under the other layer, film, region or plate, and the case where another layer, film, region or plate is inserted between the layer, film, region or plate and the other layer, film, region or plate. In addition, in this specification, when a component is referred to as being disposed "on" another component, it includes the case where the component is disposed above the other component and the case where the component is disposed below the other component.
[0046] Hereinafter, the present invention will be described in more detail.
[0047] positive electrode
[0048] In one embodiment, the present invention provides a positive electrode for a lithium secondary battery, comprising a current collector and a mixture layer formed on one surface or both surfaces of the current collector, wherein the mixture layer has a double-layer structure in which a first mixture layer and a second mixture layer are laminated, the first mixture layer comprises a positive electrode active material, a conductive material, a positive electrode additive and a binder, and when the first mixture layer is subjected to X-ray diffraction (XRD) analysis, the following expression 1 is satisfied:
[0049] [Expression 1]
[0050] A / B≤1
[0051] A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°.
[0052] The positive electrode for a lithium secondary battery of the present invention has a double-layer structure in which a first mixture layer and a second mixture layer are sequentially laminated on a current collector so that the second mixture layer is located on the outermost side.
[0053] In this case, the first mixture layer may include a positive electrode active material, a conductive material, a positive electrode additive, and a binder, wherein the positive electrode additive may be a lithium cobalt oxide represented by the following Chemical Formula 1:
[0054] [Chemical formula 1]
[0055] Li p Co (1-q) M 1 q O4
[0056] In the above chemical formula 1, M 1 It represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
[0057] Specifically, in the above chemical formula 1, M 1 represents a Zn element, and q may be 0.2≤q≤0.4.
[0058] The positive electrode additive may contain excess lithium to provide lithium for the lithium consumption caused by irreversible chemical and physical reactions occurring at the negative electrode during initial charging, thereby increasing the charge capacity of the battery and reducing the irreversible capacity of the battery, thereby improving the life characteristics of the battery.
[0059] The present invention may include lithium cobalt oxide represented by Chemical Formula 1 as a positive electrode additive. In this case, Li6CoO4, Li6Co 0.5 Zn 0.5 O4、Li6Co 0.7 Zn 0.3 O4 and the like as the lithium cobalt oxide represented by Chemical Formula 1. The lithium cobalt oxide represented by the above Chemical Formula 1 has the advantages of having a higher lithium ion content than the nickel-containing oxide commonly used in the art and a lower voltage range required for delithiation, so that lithium ions can be deintercalated without affecting the reaction of the positive electrode active material when the battery is activated.
[0060] In addition, the lithium cobalt metal oxide represented by the above chemical formula 1 may have a tetragonal crystal structure and may have a P42 / nmc space group in the tetragonal crystal structure. The lithium cobalt metal oxide represented by the above chemical formula 1 exhibits excellent charge / discharge characteristics and life characteristics in lithium secondary batteries, but has low thermal stability. Specifically, when the lithium cobalt metal oxide represented by the above chemical formula 1 is used as a positive electrode additive, when manufacturing the mixture layer of the positive electrode, structural deformation may occur under the influence of temperature such as slurry temperature, whereby the characteristics of the battery may be deteriorated.
[0061] Meanwhile, in the positive electrode for a lithium secondary battery of the present invention, deformation of the positive electrode additive due to temperature is minimized by adjusting the coating temperature of the slurry when manufacturing the positive electrode.
[0062] For example, when the first mixture layer is subjected to XRD analysis, the positive electrode for a lithium secondary battery of the present invention may satisfy the above Expression 1.
[0063] In the above expression 1, the peak appearing in the range of 2θ=47.9±0.1° and having intensity B is realized by the crystal of the lithium cobalt metal oxide represented by chemical formula 1, and the peak appearing in the range of 2θ=38.5±0.1° and having intensity A is realized by impurities. This means that the fraction of the lithium cobalt metal oxide represented by chemical formula 1 increases as the intensity ratio of the peak, i.e., "A / B", decreases. In the positive electrode of the present invention, the fraction of the lithium cobalt metal oxide represented by chemical formula 1 in the positive electrode additive contained in the first mixture layer is increased to more than 98%, so A / B can satisfy less than 1, less than 0.35, less than 0.25, or less than 0.1. In some cases, A / B can satisfy 0 because the lithium cobalt metal oxide represented by chemical formula 1 accounts for 100% of the positive electrode additive.
[0064] In addition, the content of the positive electrode additive may be 0.1 to 5 parts by weight, specifically 0.1 to 3 parts by weight, or 1 to 3 parts by weight, relative to 100 parts by weight of the total amount of the first mixture layer.
[0065] The first mixture layer is a positive electrode active material capable of reversible intercalation and deintercalation, and may include a lithium nickel composite oxide represented by Chemical Formula 2:
[0066] [Chemical formula 2]
[0067] Li x [Ni y Co z Mn w M 2 v ]O u
[0068] In the above chemical formula 2, M 2 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 <z≤0.5,0.01<w≤0.5,0≤v≤0.2,1.5≤u≤4.5。
[0069] The lithium nickel composite oxide represented by Chemical Formula 2 is a composite metal oxide containing lithium, nickel, cobalt, and manganese, and in some cases, may be doped with another transition metal M. 2 For example, the positive electrode active material may include a material selected from LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.6 Co 0.2Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 For example, in the positive electrode active material, as the lithium nickel composite metal oxide represented by Chemical Formula 2, LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0070] In addition, the content of the positive electrode active material may be 85 to 95 parts by weight, and specifically may be 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight relative to 100 parts by weight of the positive electrode mixture layer.
[0071] In this case, a conductive material can be used to improve the performance of the positive electrode such as conductivity, and the conductive material can include one or more materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber. For example, the conductive material can include acetylene black.
[0072] In addition, the content of the conductive material may be 1 to 10 parts by weight, specifically 2 to 8 parts by weight or 2 to 6 parts by weight, relative to 100 parts by weight of the first mixture layer.
[0073] In addition, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate and copolymers thereof. For example, the binder may include polyvinylidene fluoride.
[0074] In addition, the binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight or 2 to 6 parts by weight, relative to 100 parts by weight of the total amount of the first mixture layer.
[0075] In addition, the average thickness of the first mixture layer is not particularly limited, but may be specifically 0.1 to 20 μm, more specifically 0.1 to 15 μm, 0.1 to 10 μm, 2 to 10 μm, 4 to 10 μm, or 5 to 9 μm.
[0076] In addition, the second mixture layer may include a positive electrode active material, a conductive material, and a binder.
[0077] The positive electrode active material included in the second mixture layer may be used without particular limitation as long as it is a lithium nickel composite oxide represented by Chemical Formula 2, and examples of the positive electrode active material may include a material selected from the group consisting of LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 One or more compounds of the group consisting of O2.
[0078] For example, in the positive electrode active material, as the lithium nickel composite metal oxide represented by Chemical Formula 2, LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0079] In addition, the content of the positive electrode active material may be 80 to 98 parts by weight, specifically 84 to 96 parts by weight or 88 to 96 parts by weight, relative to 100 parts by weight of the second mixture layer.
[0080] In this case, the conductive material contained in the second mixture layer can be used to improve the performance of the positive electrode such as conductivity, etc., and the conductive material can include one or more materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and carbon fiber. For example, the conductive material can include acetylene black.
[0081] In addition, the content of the conductive material may be 1 to 10 parts by weight, specifically 2 to 8 parts by weight or 2 to 6 parts by weight, relative to 100 parts by weight of the second mixture layer.
[0082] In addition, the binder included in the second mixture layer may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate and copolymers thereof. For example, the binder may include polyvinylidene fluoride.
[0083] In addition, the content of the binder may be 1 to 10 parts by weight, specifically 2 to 8 parts by weight or 2 to 6 parts by weight, relative to 100 parts by weight of the second mixture layer.
[0084] In addition, the second mixture layer may have an average thickness of 50 to 300 μm, specifically 100 to 200 μm, 80 to 150 μm, 120 to 170 μm, 150 to 300 μm, 200 to 300 μm, or 150 to 190 μm.
[0085] In a specific example, the thickness of the second mixture layer may be greater than the thickness of the first mixture layer.
[0086] Meanwhile, in the positive electrode for lithium secondary batteries of the present invention, a material having high conductivity and not causing chemical changes in the battery can be used for the current collector. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of using aluminum or stainless steel, a material surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, in order to improve the adhesion of the positive electrode active material, the surface of the current collector can form a fine irregular body, and can be formed into various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a non-woven body, etc. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the positive electrode current collector can be appropriately applied to be 3 μm to 500 μm.
[0087] Positive electrode manufacturing method
[0088] In addition, in one embodiment, the present invention provides a method for manufacturing a positive electrode for a lithium secondary battery, the method comprising coating a first slurry containing a positive electrode active material, a positive electrode additive, a conductive material and a binder on one or both surfaces of a current collector to form a first mixture layer, and coating a second slurry containing a positive electrode active material, a conductive material and a binder on the current collector formed with the first mixture layer to form a second mixture layer, wherein the formation of the first mixture layer comprises a process of controlling the temperature of the first slurry to be below 40° C., the formation of the second mixture layer comprises a process of controlling the temperature of the second slurry to be below 40° C., and when performing XRD analysis on the first mixture layer, the following expression 1 is satisfied:
[0089] [Expression 1]
[0090] A / B≤1
[0091] A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°.
[0092] In the method for manufacturing a positive electrode for a lithium secondary battery of the present invention, a first mixture layer and a second mixture layer are sequentially formed on a current collector so that the second mixture layer is located at the outermost side, wherein, in the process of forming the first mixture layer, the deformation of the positive electrode additive contained in the first mixture layer can be minimized by controlling the temperature of the first slurry. Therefore, the structural deformation of the positive electrode additive contained in the positive electrode can be prevented, thereby preventing the degradation of the battery characteristics.
[0093] Here, controlling the temperature of the slurry may refer to controlling an ambient temperature when the slurry is coated on a current collector, and specifically, may refer to controlling a temperature inside a reactor storing the slurry when the slurry is coated on a current collector.
[0094] For example, the formation of the first mixture layer and the formation of the second mixture layer are each performed at a temperature of 10°C to 40°C. Specifically, when forming the first mixture layer, when the first slurry is coated on the current collector, the temperature of the reactor storing the first slurry can be controlled within the range of 10°C to 40°C, more specifically, it can be controlled within the range of 10°C to 30°C, 10°C to 20°C, 15°C to 25°C, 22°C to 28°C, 20°C to 30°C, or 18°C to 25°C. When forming the first mixture layer and forming the second mixture layer, when the temperature of the first or second slurry is controlled to be lower than 10°C, the slurry may not be uniformly coated on the current collector, and when the temperature of the first or second slurry is controlled to be higher than 40°C, the positive electrode additive contained in the first slurry may be deformed. Therefore, when forming the first mixture layer and forming the second mixture layer, the temperature of the first slurry and the temperature of the second slurry can be controlled within the above ranges, respectively.
[0095] In addition, the manufacturing method of the positive electrode for lithium secondary batteries of the present invention may include a first rolling operation of rolling the first mixture layer after forming the first mixture layer and a second rolling operation of rolling the second mixture layer after forming the second mixture layer. In a specific example, in the manufacturing method of the positive electrode for lithium secondary batteries of the present invention, two rolling processes may be performed, including a rolling process of the first mixture layer using a roller press before forming the second mixture layer and a rolling process of the second mixture layer after forming the second mixture layer.
[0096] Here, the first rolling operation can make the thickness of the first mixture layer uniform, and the temperature can be controlled when rolling, so that the deformation of the positive electrode additive can be minimized. To this end, the first rolling operation can be performed at a low temperature and can be performed at a lower speed than the second rolling operation. Specifically, the first rolling operation can be performed at a temperature of 10°C to 40°C, 10°C to 30°C, 10°C to 20°C, 15°C to 25°C, 22°C to 28°C, 20°C to 30°C or 18°C to 25°C, similar to the above-described control of the slurry temperature when forming the mixture layer. In addition, the first rolling operation can be performed at a rolling speed of 0.5m / s to 6m / s, and specifically can be performed at a rolling speed of 0.5m / s to 5.5m / s, 0.5m / s to 5m / s, 0.5m / s to 4.5m / s, 0.5m / s to 4m / s, 0.5m / s to 3.5m / s, 0.7m / s to 3m / s, 0.7m / s to 2.5m / s, 0.7m / s to 2m / s, 0.9m / s to 2m / s, 1m / s to 1.5m / s, 1m / s to 1.2m / s, 2m / s to 5m / s, 2m / s to 5.5m / s or 3m / s to 5m / s.
[0097] In addition, the second rolling operation can be performed at a higher temperature and a higher speed than the first rolling operation. Specifically, the second rolling operation can be performed at a temperature of 50°C to 100°C, more specifically, at a temperature of 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C. Specifically, the second rolling operation can be carried out at a rolling speed of 2m / s to 7m / s, more specifically, it can be carried out at a rolling speed of 2m / s to 6.5m / s, 2m / s to 6m / s, 2m / s to 5.5m / s, 2m / s to 5m / s, 2m / s to 4.5m / s, 2m / s to 4m / s, 2.5m / s to 4m / s, 2.5m / s to 3.5m / s, 3.5m / s to 5m / s, 5m / s to 7m / s, 5.5m / s to 6.5m / s or 6m / s to 7m / s.
[0098] In addition, the first rolling operation and the second rolling operation can each be carried out under a pressure of 50MPa to 200MPa, specifically under a pressure of 50MPa to 150MPa, 50MPa to 100MPa, 100MPa to 200MPa, 150MPa to 200MPa, or 80MPa to 140MPa. In this case, in order to optimize the rolling density of the first mixture layer, the first rolling operation can be carried out under the same pressure as the second rolling operation, or can be carried out under a pressure of less than 2 times the pressure in the second rolling operation, for example, less than 1.5 times, less than 1.2 times, or 1.1 times to 1.4 times the pressure in the second rolling operation. Therefore, the ratio (D1: D2) of the average thickness D1 of the first mixture layer to the average thickness D2 of the second mixture layer can be 4: 6 to 1: 10. Specifically, the ratio (D1: D2) of the average thickness of the first and second positive electrode mixture layers can be 3: 7 to 1: 10 or 2: 8 to 1: 9. In the present invention, the second mixture layer is formed relatively thick, thereby increasing the bonding force with the current collector and increasing the stability of the electrode.
[0099] According to the present invention, the first mixture layer and the second mixture layer can be sequentially formed on the current collector under the same temperature and rolling conditions as above, and thus a positive electrode containing a positive electrode additive with minimal deformation can be manufactured.
[0100] Therefore, when the first mixture layer is subjected to XRD analysis, the positive electrode manufactured by the method for manufacturing a positive electrode for a lithium secondary battery according to the present invention may satisfy the above Expression 1.
[0101] Lithium secondary battery
[0102] In addition, in one embodiment, the present invention provides a lithium secondary battery including the positive electrode, negative electrode, and separator between the positive and negative electrodes of the present invention as described above.
[0103] The lithium secondary battery of the present invention may include the positive and negative electrodes of the present invention as described above and has a structure in which the positive and negative electrodes are impregnated with an electrolyte containing a lithium salt.
[0104] Here, the negative electrode may include a negative electrode current collector and a negative electrode mixture layer located on the negative electrode current collector and containing a negative electrode active material. Specifically, the negative electrode can be manufactured by coating, drying, and pressing the negative electrode active material on the negative electrode current collector, and may also contain, as needed, the conductive material, organic binder polymer, filler, etc. as described above.
[0105] In addition, examples of the negative electrode active material may include: carbon and graphite materials, such as graphite having a completely layered crystal structure like natural graphite, soft carbon having a low crystallinity layered crystal structure (graphene structure; a structure in which hexagonal honeycomb planes of carbon are arranged in layers), hard carbon in which these structures are mixed with an amorphous part, artificial graphite, expanded graphite, carbon fiber, hardly graphitizable carbon, carbon black, carbon nanotubes, fullerenes, activated carbon, etc.; metal composite oxides, such as Li x Fe2O3(0 ≤ x ≤ 1), Li x WO2(0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Groups 1, 2, 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc.; lithium metal, lithium alloy, silicon-based alloy, tin-based alloy; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, etc.; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc.
[0106] For example, the negative electrode active material may include graphite and silicon (Si)-containing particles. The graphite may include one or more of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure, and the silicon (Si)-containing particles are particles mainly containing silicon (Si) as a metal component, and may include silicon (Si) particles, silicon dioxide (SiO2) particles, or a mixture of silicon (Si) particles and silicon dioxide (SiO2) particles.
[0107] In this case, the negative electrode active material may include 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si) particles relative to a total of 100 parts by weight. In the present invention, by adjusting the amount of graphite and silicon (Si) particles contained in the negative electrode active material within the above range, the charge capacity per unit mass can be increased while reducing lithium consumption and irreversible capacity loss during initial charge and discharge of the battery.
[0108] In addition, the negative electrode mixture layer may have an average thickness of 100 to 200 μm, specifically, the average thickness may be 100 to 180 μm, 100 to 150 μm, 120 to 200 μm, 140 to 200 μm, or 140 to 160 μm.
[0109] In addition, the negative electrode current collector is not particularly limited to any current collector as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and when copper or stainless steel is used, materials surface-treated with carbon, nickel, titanium, silver, etc. can be used.
[0110] In addition, like the positive electrode current collector, the negative electrode current collector may be formed with fine irregularities on its surface to enhance the binding force with the negative electrode active material, and may be formed in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, a non-woven body, etc. In addition, considering the conductivity and the total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector may be appropriately applied to be 3 μm to 500 μm.
[0111] In addition, the separator is between the positive electrode and the negative electrode, and an insulating film with high ion permeability and mechanical strength is used. The separator is not particularly limited as long as it is commonly used in the art, and specifically a sheet or non-woven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber, polyethylene, etc. can be used, and in some cases, a composite separator in which a porous polymer material such as a sheet or non-woven fabric is coated with inorganic particles / organic particles by an organic binder polymer can be used. In the case of using a solid electrolyte such as a polymer as an electrolyte, the solid electrolyte can also serve as a separator. In addition, the separator can have a hole with an average diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0112] Meanwhile, the positive electrode and the negative electrode may be wound in a jelly roll form and accommodated in a cylindrical battery, a prismatic battery, or a pouch type battery, or accommodated in a pouch type battery in a folded or stack-folded form, but the present invention is not limited thereto.
[0113] In addition, the lithium salt-containing electrolyte of the present invention may be composed of an electrolyte and a lithium salt, and examples of the lithium salt-containing electrolyte may include a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, and the like.
[0114] Examples of the non-aqueous organic solvent may include aprotic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfranc, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, ethyl propionate, and the like.
[0115] Examples of the organic solid electrolyte may include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, poly-agitated lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymer materials containing ion dissociative groups, and the like.
[0116] Examples of inorganic solid electrolytes may include Li nitrides, halides, sulfates, and the like, such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, and the like.
[0117] Lithium salts are materials that are easily soluble in non-aqueous electrolytes. Examples of lithium salts may include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2Nli, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, imide, etc.
[0118] In addition, in order to improve the charge and discharge characteristics, flame retardancy, etc., pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, etc. may be added to the electrolyte. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride and trifluoroethylene may be further included, and in order to improve high-temperature storage characteristics, carbon dioxide gas may be further included, and fluoroethylene carbonate (FEC), propylene sultone (PRS), etc. may be further included.
[0119] Meanwhile, in one embodiment, the present invention provides a battery module including the above-mentioned secondary battery as a unit battery, and provides a battery pack including the battery module.
[0120] The battery pack can be used as a power source for large and medium-sized equipment that requires high temperature stability, long cycle characteristics and high rate characteristics. Specific examples of large and medium-sized equipment may include power tools driven by motors, electric vehicles (including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) and the like), electric two-wheeled vehicles (including electric bicycles (E-bikes) and electric scooters (E-scooters)), electric golf carts, power storage systems, and the like, and more specifically may include HEVs, but the present invention is not limited thereto.
[0121] Example
[0122] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples.
[0123] However, the following examples and comparative examples are only for illustrating the present invention, and the contents of the present invention are not limited to the examples and comparative examples described below.
[0124] Examples 1 to 4 and Comparative Examples 1 to 7. Production of positive electrode for lithium secondary battery
[0125] Weigh 95 parts by weight of LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, 0.9 parts by weight of Li6CoO4 as a positive electrode additive, 1.6 parts by weight of PVdF as a binder, and 2.5 parts by weight of carbon black as a conductive material were mixed in an N-methylpyrrolidone (NMP) solvent to prepare a first slurry for a first mixture layer.
[0126] In addition, 95 parts by weight of LiNi as a positive electrode active material was weighed. 0.8 Co 0.1 Mn 0.1 O2, 2 parts by weight of PVdF as a binder, and 3 parts by weight of carbon black as a conductive material were mixed in an NMP solvent to prepare a second slurry for a second mixture layer.
[0127] The first slurry was coated on an aluminum foil and dried, and then a first rolling operation was performed to form a first mixture layer (average thickness: 8 μm). Subsequently, a second slurry was coated on the first mixture layer and dried, and then a second rolling operation was performed to form a second mixture layer (average thickness: 100 μm).
[0128] In this case, conditions for performing the first and second mixture layer forming operations and the first and second roll pressing operations are as shown in Table 1 below.
[0129] [Table 1]
[0130]
[0131] Experimental Example 1
[0132] 1) XRD pattern observation of the first mixture layer
[0133] In order to confirm the change of positive electrode additives with temperature when manufacturing positive electrodes for lithium secondary batteries, the first mixture layer of the positive electrodes for lithium secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was subjected to XRD measurement, and the fraction of lithium cobalt metal oxide contained in each positive electrode additive was calculated from the measured XRD. In this case, the XRD was measured using a Rigaku XRD analyzer, and the scanning wavelength (CuKα radiation, 40 kV, 100 mA), and the XRD patterns were obtained in the range of 15° to 64° in 2θ and a scanning speed of 5° / sec.
[0134] As a result, peaks of Li6CoO4 were observed in the first mixture layer of each of Examples 1 to 4. Specifically, a peak of intensity A was observed in the range of 2θ=38.5±0.1°, and a peak of intensity B was observed in the range of 2θ=47.9±0.1°. For reference, A / B of each of Examples 1 to 4 was 0.1 or less.
[0135] On the other hand, the peak appearing in the examples was not observed in each of Comparative Examples 1 to 4. It is considered that the structure of the positive electrode additive was deformed due to the high temperature in the mixture layer forming operation and the roll pressing operation when manufacturing the positive electrode.
[0136] Experimental Example 2
[0137] In order to evaluate the performance of the positive electrode for a lithium secondary battery of the present invention, an experiment was conducted as follows.
[0138] 1) Initial resistance value evaluation
[0139] A lithium secondary battery is manufactured using each positive electrode manufactured in the embodiment and the comparative example. Specifically, natural graphite, carbon black conductive material and PVdF binder as negative electrode active materials are mixed in a weight ratio of 85:10:5 in an NMP solvent to prepare a negative electrode forming slurry, and the negative electrode forming slurry is coated on a copper foil to manufacture a negative electrode. A diaphragm (thickness: about 16 μm) made of a porous polyethylene (PE) film is laminated to be placed between each positive electrode manufactured in the embodiment and the comparative example and the negative electrode manufactured above to manufacture an electrode assembly. After the manufactured electrode assembly is placed in a battery case, an electrolyte is injected into the shell to manufacture a lithium secondary battery. In this case, an electrolyte is prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0M in an organic solvent consisting of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (the mixed volume of EC / DMC / EMC is 3 / 4 / 3).
[0140] Then, each lithium secondary battery manufactured as described above was charged with a constant current (CC) so that the battery voltage reached 4.2V at a rate of 0.3C and a current of 333mA in a constant current-constant voltage (CC-CV) mode, and each lithium secondary battery was charged once by cutting off the current at 0.05C while maintaining a constant voltage (CV) of 4.2V after the battery voltage reached 4.2V. The battery charged for the first time was discharged with a constant current (CC) of 333mA and a rate of 0.3C until the battery voltage reached 3V, which was set as one cycle, and repeated three times, and the voltage drop occurring when discharged at a current of 2A (2C) for 10 seconds was recorded, and then the direct current (DC) discharge resistance value measured during the initial evaluation was calculated using R=V / I (Ohm's law), as shown in Table 2 below. In this case, the DC resistance is closely related to the output characteristics of the secondary battery.
[0141] 2) Cycle life performance evaluation
[0142] In the same manner as the initial resistance value evaluation, a lithium secondary battery was manufactured using the positive electrode manufactured in the embodiment and the comparative example. For each manufactured lithium secondary battery, the capacity retention rate was measured while performing 100 charge and discharge (n=100) and 200 charge and discharge (n=200) at 25°C under the conditions of a final charge voltage of 4.25V, a final discharge voltage of 2.5V and 0.5C / 0.5C. At this time, the capacity retention rate was calculated using the following expression 2, and the calculation results are shown in Table 2 below:
[0143] [Expression 2]
[0144] Capacity retention rate (%) = (discharge capacity at n charge and discharge times / discharge capacity at one charge and discharge) × 100
[0145] [Table 2]
[0146]
[0147] As shown in Table 2, it is confirmed that the resistance value of the lithium secondary battery manufactured in each embodiment is lower than the resistance value of each comparative example. In particular, the resistance value of the lithium secondary battery containing the positive electrode of Comparative Examples 1 to 4 is the highest. This is believed to be due to the structural deformation of the positive electrode additive caused by the high temperature in the mixture layer formation operation and the rolling operation when manufacturing the positive electrode. In addition, it was found that the electrical performance of the battery with the positive electrode of the embodiment was improved, and the capacity retention rate at 100 and 200 times of charge and discharge was as high as 97% and 95%, respectively. On the other hand, it was confirmed that in Comparative Example 5, the porosity of the first mixture layer was too small to allow the electrolyte to penetrate into the surface of the current collector, so the electrical performance of the battery was reduced. In addition, it was confirmed that in the battery containing the positive electrode of Comparative Examples 6 and 7, the porosity of the first mixture layer was significantly reduced, so the electrical performance of the battery was reduced.
[0148] The above results confirm that in the positive electrode for the lithium secondary battery of the present invention, the first mixture layer and the second mixture layer are arranged on the current collector, the coating temperature of the slurry is adjusted when the positive electrode is manufactured, and the first mixture layer is rolled under specific conditions before the second mixture layer is formed, thereby minimizing the deformation of the positive electrode additive contained in the first mixture layer, and thus achieving high battery performance.
[0149] Although exemplary embodiments of the present invention and their advantages are described above in detail, those skilled in the art should understand that various changes, substitutions and alterations may be made herein without departing from the scope of the invention as defined by the appended claims.
[0150] Therefore, the technical scope of the present invention should not be limited to the contents described in the specific description of the specification, but should be defined by the appended claims.
Claims
1. A method for manufacturing a positive electrode for a lithium secondary battery, the method comprising: Applying a first slurry containing a positive electrode active material, a positive electrode additive, a conductive material, and a binder on one surface or both surfaces of a current collector to form a first mixture layer; and coating a second slurry containing a positive electrode active material, a conductive material and a binder on the current collector formed with the first mixture layer to form a second mixture layer, wherein the forming of the first mixture layer and the forming of the second mixture layer respectively include a process of controlling the temperature of the first slurry to be between 10°C and 40°C and a process of controlling the temperature of the second slurry to be between 10°C and 40°C, and When the first mixture layer is subjected to X-ray diffraction (XRD) analysis, the following Expression 1 is satisfied: [Expression 1] A / B≤1 A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°. Wherein, the positive electrode additive is lithium cobalt oxide represented by the following chemical formula 1: [Chemical formula 1] Li p Co (1-q) M 1 q O4 In the above chemical formula 1, M 1 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively, and The peak appearing in the range of 2θ=47.9±0.1° and having intensity B is realized by the crystal of the lithium cobalt oxide represented by Chemical Formula 1, and the peak appearing in the range of 2θ=38.5±0.1° and having intensity A is realized by impurities.
2. The method of claim 1, wherein: The forming of the first mixture layer and the forming of the second mixture layer include a process of controlling the temperature of the first slurry to be between 10° C. and 30° C. and a process of controlling the temperature of the second slurry to be between 10° C. and 30° C., respectively.
3. The method of claim 1, further comprising: After forming the first mixture layer, performing a first rolling operation on the first mixture layer; and After forming the second mixture layer, a second rolling operation of rolling the second mixture layer is performed.
4. The method of claim 3, wherein: The first rolling operation is performed at a speed of 0.5 m / s to 6 m / s; The second rolling operation is performed at a speed of 2 m / s to 7 m / s; and The second rolling operation is performed at a speed greater than the first rolling operation.
5. The method of claim 3, wherein: The first rolling operation is performed at a temperature of 10°C to 40°C; and The second rolling operation is performed at a temperature of 40°C to 100°C.
6. A positive electrode for a lithium secondary battery, comprising a current collector and a mixture layer formed on one surface or both surfaces of the current collector, in, The mixture layer has a double-layer structure in which a first mixture layer and a second mixture layer are laminated, The first mixture layer comprises a positive electrode active material, a positive electrode additive, a conductive material and a binder, and When the first mixture layer is subjected to X-ray diffraction (XRD) analysis, the following Expression 1 is satisfied: [Expression 1] A / B≤1 A represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=38.5±0.1°, and B represents the intensity of the strongest peak among the peaks appearing in the range of 2θ=47.9±0.1°. Wherein, the positive electrode additive is lithium cobalt oxide represented by the following chemical formula 1: [Chemical formula 1] Li p Co (1-q) M 1 q O4 In the above chemical formula 1, M 1 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively, and The peak appearing in the range of 2θ=47.9±0.1° and having intensity B is realized by the crystal of the lithium cobalt oxide represented by Chemical Formula 1, and the peak appearing in the range of 2θ=38.5±0.1° and having intensity A is realized by impurities.
7. The positive electrode according to claim 6, wherein The positive electrode additive has a tetragonal structure with a space group of P42 / nmc.
8. The positive electrode according to claim 6, wherein The content of the positive electrode additive is 0.1 wt % to 5 wt % relative to the total weight of the first mixture layer.
9. The positive electrode according to claim 6, wherein The positive electrode active material is a lithium nickel composite oxide represented by the following chemical formula 2: [Chemical formula 2] Li x [Ni y Co z Mr w M 2 v ]O u In the above chemical formula 2, M 2 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 <z≤0.5,0.01<w≤0.5,0≤v≤0.2,1.5≤u≤4.5。 10. The positive electrode according to claim 6, wherein: The average thickness D1 of the first mixture layer is 0.1 μm to 20 μm; and The average thickness D2 of the second mixture layer is 50 μm to 300 μm.
11. A lithium secondary battery, comprising: The positive electrode according to claim 6; negative electrode; and A separator is interposed between the positive electrode and the negative electrode.
12. The lithium secondary battery according to claim 11, wherein The negative electrode includes a negative electrode current collector and a negative electrode mixture layer located on the negative electrode current collector and containing a negative electrode active material. Wherein, the negative electrode active material comprises carbon material and silicon material.
13. The lithium secondary battery according to claim 12, wherein: The silicon material may be contained in an amount of 1 part by weight to 20 parts by weight relative to 100 parts by weight of the negative electrode mixture layer.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2019061751A
Manufacturing method of cobalt aluminum oxide
KR1020210071225A
Positive electrode additive, manufacturing method therefor and positive electrode and lithium secondary battery comprising same
CN111226334A
Method for preparing cathode additive for lithium secondary battery, and cathode additive for lithium secondary battery, prepared thereby
CN112218829A